An Overview of Golgi Membrane-Associated Degradation (GOMED) and Its Detection Methods - Hajime Tajima Sakurai; Satoko Arakawa; Hirofumi Yamaguchi; Satoru Torii; Shinya Honda; Shigeomi Shimizu (Cells, 2023)
Autophagy is a cellular mechanism that utilizes lysosomes to degrade its own components and is performed using Atg5 and other molecules originating from the endoplasmic reticulum membrane. On the other hand, we identified an alternative type of autophagy, namely, Golgi membrane-associated degradation (GOMED), which also utilizes lysosomes to degrade its own components, but does not use Atg5 originating from the Golgi membranes. The GOMED pathway involves Ulk1, Wipi3, Rab9, and other molecules, and plays crucial roles in a wide range of biological phenomena, such as the regulation of insulin secretion and neuronal maintenance. We here describe the overview of GOMED, methods to detect autophagy and GOMED, and to distinguish GOMED from autophagy.